Benjamin Frankel (ed.), Roots of Realism og Realism: Restatements and Renewal, London og Portland, Oregon: Frank Cass (Cass Series on Security Studies), 1996, 415 og 456 s., GBP 35.00 pr. stk. (hardback). - Brems Knudsen, Tonny (Politica, 1997)
-